Ethnographic peculiarities of Ukrainian people and their role in creating ecovillages in Ukraine - Писаренко, П. В.; Гармаш, О. І. (Scientific Progress & Innovations, 2016)
The article deals with ethnographic peculiarities of Ukrainian people as descendants of Trypillian culture farmers. We analyzed the main achievements of Ukrainian farmers of nineteenth century as representatives of agriculture, which has not undergone the harmful effects of scientific and technological revolution. We give the information about «Springs Valley» as one of the largest ecovillages of Ukraine, embodying certain features of traditional Ukrainian life and achievements of scientific and technological progress. We give the definition of Trypillian culture, ecovillage, village, farmstead, house. We also give our own definition of «ecovillage».